Bioinformatics Analysis of Actin Molecules: Why Quantity Does Not Translate Into Quality? - Glyakina, Anna V.; Galzitskaya, Oxana V. (Frontiers in Genetics, 2020)
It is time to review all the available data and find the distinctive characteristics of actin that make it such an important cell molecule. The presented double-stranded organization of filamentous actin cannot explain the strong polymorphism of actin fibrils. In this work, we performed bioinformatics analysis of a set of 296 amino acid actin sequences from representatives of different classes of the Chordate type. Based on the results of the analysis, the degree of conservatism of the primary structure of this protein in representatives of the Chordate type was determined. In addition, 155 structures of rabbit actin obtained using X-ray diffraction analysis and electron microscopy have been analyzed over the past 30 years. From pairwise alignments and the calculation of root-mean-square deviations (RMSDs) for these structures, it follows that they are very similar to each other without correlation with the structure resolution and the reconstruction method: the RMSDs for 11,781 pairs did not exceed 3 Å. It turned out that in rabbit actin most of the charged amino acid residues are located inside the protein, which is not typical for the protein structure. We found that two of six exon regions correspond to structural subdomains. To test the double-stranded organization of the actin structure, it is necessary to use new approaches and new techniques, taking into account our new data obtained from the structural analysis of actin.